Ուրարտու պետության կազմավորումը, հզորացումը և կործանումը - Խաչատրյան, Վալերի («Զանգակ - 97»)
The Heartland of the Urartian State - Van Lake basin probably had a population of about a hundred thousand people. From the formation of the Urartian State a mass of Human population under the pressure of the Assyrian Empire migrated and found safe haven within the borders of the Urartian State. Many of them were called up for military Service and look place in the campaigns of the Urartian Kings, thus, having sufficient contribution in the success of the Kingdom. From the beginning of the first quarter of the seventh Century the migration of the Hurrian potential military forcc to Urartu for some reasons came to an end. This factor had a fatal role among the reasons of the downfall of the Kingdom.
Keywords: Հայոց պատմություն